2012
DOI: 10.1177/1933719111424451
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of GSTT1 and GSTM1 Polymorphisms on Human Male Infertility in North Indian Population

Abstract: Genes of different pathways regulate spermatogenesis, and complexity of spermatogenic process indicates that polymorphisms or mutations in these genes could cause male infertility. Detoxification pathway is involved in the regulation of spermatogenesis by reducing oxidative stress and contributes to the maintenance of global methylation in concert with other pathways. Glutathione S-transferases (GSTs) belong to the family of phase II antioxidant enzymes involved in the cellular detoxification of various physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
3
16
0
1
Order By: Relevance
“…70 Results from animal studies indicate that insulin has the potential to rescue spermatogenesis in type 1 diabetic mice 74 as well as increase sperm motility and sperm concentration in rats. 9 Furthermore, it has been demonstrated that IGF-1 protects equine Leydig cells from undergoing apoptosis in vitro. 75 Spermatogenesis is an active cell division process that requires insulin and IGF-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 Results from animal studies indicate that insulin has the potential to rescue spermatogenesis in type 1 diabetic mice 74 as well as increase sperm motility and sperm concentration in rats. 9 Furthermore, it has been demonstrated that IGF-1 protects equine Leydig cells from undergoing apoptosis in vitro. 75 Spermatogenesis is an active cell division process that requires insulin and IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Several different disorders can cause male infertility, including idiopathic oligospermia (low sperm counts, for which a specific treatment remains unknown), [3][4][5][6] complete asthenozoospermia (absence of sperm motility; implicated in 19% of infertile cases), 7 and isolated asthenozoospermia (low sperm motility, caused by sperm dysfunction, varicocele, infection, or genetic factors; implicated in 24% of infertile cases). [8][9][10] In the 1970s, several purported causes of male factor infertility received considerable attention. As a consequence, the World Health Organization published both new standardized diagnostic approaches toward male factor infertility 11 and standardized techniques of semen analysis.…”
Section: Introductionmentioning
confidence: 99%
“…4. DISCUSSION Twenty-four percent of infertile men present with isolated AZS (14) caused by various factors including varicocele, infection or genetic causes (15)(16)(17). Many cases are however idiopathic in nature and no specific causes can be ascribed to the condition (18).…”
Section: Validation Of Pathways By Clustering Proteins By Self Organimentioning
confidence: 99%
“…The characteristics of selected studies are summarized in Table 1. A total of 12 eligible studies met the inclusion criteria, including 11 studies for GSTM1 [14,15,[25][26][27][28][29][30][31][32][33] and 9 ones for GSTT1 [17,26,27,[29][30][31][32][33]. All the included studies were case-control studies.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%